Ammonium Nitrogen Tolerant Chlorella Strain Screening and Its Damaging Effects on Photosynthesis - Wang, Jie; Zhou, Wei; Chen, Hui; Zhan, Jiao; He, Chenliu; Wang, Qiang (Frontiers in Microbiology, 2019)
Nitrogen is an essential nutrient element. Ammonium nitrogen, one of the most common nitrogen sources, is found in various habitats, especially wastewater. However, excessive amounts of ammonium nitrogen can be toxic to phytoplankton, higher plants, fish and other animals, and microorganisms. In this study, we explored the tolerance of green algae to ammonium nitrogen using 10 Chlorella strains. High concentrations of ammonium nitrogen directly inhibited the growth of Chlorella, but the degree of inhibition varied by strain. With the EC50 of 1.6 g L1 and 0.4 g L1, FACHB-1563 and FACHB-1216 respectively had the highest and lowest tolerance to ammonium nitrogen among all strains tested, suggesting that FACHB-1563 could potentially be used to remove excess ammonium nitrogen from wastewater in bioremediation efforts. Two strains with the highest and lowest tolerance to ammonium nitrogen were selected to further explore the inhibitory effect of ammonium nitrogen on Chlorella. Analysis of chlorophyll fluorescence, oxygen evolution, and photosynthesis proteins via immunoblot showed that photosystem II (PSII) had been damaged when exposed to high levels of ammonium nitrogen, with the oxygen-evolving complex as the primary site, and electron transport from QA to QB was subsequently inhibited by this treatment. A working model of ammonium nitrogen competition between N assimilation and PSII damage is proposed to elucidate that the assimilation rate of ammonium nitrogen by algae strains determines the tolerance of cells to ammonium nitrogen toxicity.